Process, dynamics and bioeffects of acoustic droplet vaporization induced by dual-frequency focused ultrasound - Yubo Zhao; Yi Feng; Liang Wu (Ultrasonics Sonochemistry)
Acoustic droplet vaporization (ADV) plays a crucial role in ultrasound-related biomedical applications. While previous models have examined the stages of nucleation, growth, and oscillation in isolation, which may limit their ability to fully describe the entire ADV process. To address this, our study developed an integrated model that unifies these three stages of ADV, stimulated by a continuous nonlinear dual-frequency ultrasound wave. Using this integrated model, we investigated the influence of nonlinear dual-frequency ultrasound parameters on ADV dynamics and bioeffects by incorporating tissue viscoelasticity through parametric studies. Our results demonstrated that the proposed model accurately captured the entire ADV process, ensuring continuous vapor bubble formation and evolution throughout the phase transition process. Moreover, the applied unified theory for bubble dynamics can simulate intense bubble collapse with high Mach Number as a result of the nonlinear effects of dual-frequency ultrasound. In addition, cavitation-associated mechanical and thermal damage appeared to be more strongly correlated with rapid bubble collapse than with maximum bubble size. Our research also revealed that the mechanical and thermal effects could be regulated independently to some extent by adjusting dual-frequency ultrasound parameters, as they presented differing sensitivities to frequency and acoustic power. Importantly, dual-frequency combinations such as 1.5 MHz + 3 MHz (fundamental and second harmonic), which exhibit a higher Degree of Nonlinearity (DoN) can extend bubble lifespan, offering a potential pathway to the efficacy of ultrasound treatments.